Effects of Modified Pyramid System on Muscular Strength and Hypertrophy in Older Women - dos Santos, Leandro; Ribeiro, Alex S.; Cavalcante, Edilaine F.; Nabuco, Hellen C.; Antunes, Melissa; Schoenfeld, Brad J.; Cyrino, Edilson S. (International Journal of Sports Medicine, 2018)
This study aimed to analyze the effects of a pyramid system performed with two repetition zones on muscular strength and skeletal muscle mass (SMM) in older women. Thirty-nine physically independent older women (67.8±5.4 years) were randomly assigned into one of two of groups that performed an 8-week resistance training program in an ascending pyramid fashion. Both groups performed 3 sets: a narrow repetition zone (NPR, n=20) with 12/10/8 repetitions, and a wide repetition zone (WPR, n=19) with 15/10/5 repetitions. The program consisted of 8 whole-body exercises, performed 3 times a week. Dual-energy X-ray absorptiometry was used to measure SMM, and muscular strength was evaluated by one-repetition maximum (1RM). Both groups increased (P<0.05) SMM (NPR=+ 4.7%, effect size=+ 0.34; WPR=+ 8.4%, effect size=+ 0.77), and total strength (NPR=+ 11.3%, effect size=+ 0.80; WPR=+ 13.8%, effect size=0.84), without statistical differences between them. Results suggest that both zones of repetitions in a pyramid system are effective strategies to improve muscular strength and muscle growth in older women.
Keywords: aging; strength training; pyramidal system; resistance exercises; hypertrophy